(untitled) (Research, Society and Development, 2022)
The objective is to know what adolescents know about safe sexual practices and their benefits. This is a field research with a quantitative approach, to be developed from a questionnaire with open questions, carried out at Escola Estadual de Ensino Médio Mário Brazil, located in the city of Garrafão do Norte, state of Pará, in which it attended 1033 students regularly enrolled in 2018. The survey was carried out with adolescents of both sexes aged between 15 and 19 years old, in the months of August and September 2019. 337 questionnaires were analyzed, this being divided into two axes, the first with personal information and the second with the assessment of adolescents’ knowledge about contraception. With the study in question, it is expected that there will be more visibility on the lack of knowledge of adolescents about contraceptive methods, in order to carry out health education for this public, since sexual life begins earlier and earlier.